Mesophase pitch and preparation method thereof
Through catalytic polycondensation method and weak magnetic field-assisted thermal deposition process, combined with quinoline extraction and reduced pressure distillation and purification, the problem of ash impurities in catalytic cracked oil slurry affecting the quality of mesophase bitumen, achieving the preparation of high-quality mesophase bitumen and the performance improvement of carbon materials.
Patent Information
- Application Number
- CN202311067945.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively use catalytic cracked oil slurry to prepare high-quality mesophase asphalt, mainly due to the tiny solid particles and complex composition in the raw materials, resulting in poor processability of mesophase asphalt and carbon material performance.
The catalytic polycondensation method is used to mix the catalytic cracked oil slurry with magnetic organic iron macromolecular complex and heteropolyate iron salt catalyst, and conduct a high-temperature and high-pressure reaction. Then, solid impurities are separated by a weak magnetic field-assisted heat precipitation process, and high-quality mesophase asphalt is purified by quinoline extraction and reduced pressure distillation.
Effective removal of ash impurities in catalytic cracked oil slurry is achieved, and high-quality mesophase asphalt with softening points of 220-300°C, low impurity content and wide-area streamlined optical texture is obtained, which is suitable for the preparation of carbon materials with excellent performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum deep processing technology and carbonaceous mesophase material research, and specifically relates to a mesophase asphalt, and further discloses a preparation method thereof. Background Art
[0002] With the heavy process of global crude oil resources, more and more heavy residual oils with complex compositions are produced in the process of petroleum refining, including vacuum residue, catalytic cracking slurry, ethylene tar, etc. These heavy oils are difficult to process for secondary processing, and the use of traditional processes will not only pollute the environment but also have poor economic benefits. However, these heavy residual oils are rich in a large number of aromatic components and are potential high-quality raw materials for the preparation of mesophase asphalt. At present, using mesophase asphalt as a precursor and converting it into more cost-effective carbon materials, such as carbon fiber, foamed carbon, needle coke, etc., and then using it in composite materials, energy storage, environmental protection and other fields has become a hot topic of continuous concern in the world's oil refining industry. Therefore, the production of high-quality mesophase asphalt products is of great significance for the development of carbon materials with excellent performance.
[0003] Studies have found that it is often difficult to produce high-quality carbon materials from mesophase asphalt products made using conventional heat treatment processes using catalytic cracking (FCC) oil slurry as raw materials. This is mainly because, although the catalytic cracking (FCC) oil slurry is rich in a large number of aromatic components, there are also a certain amount of tiny solid particles (such as catalyst powder) in the oil slurry. After heat treatment, these solid impurities will be "inherited" to the mesophase asphalt, thereby affecting the processability of the mesophase asphalt and the performance of the corresponding carbon materials. In addition, due to the complex composition of the catalytic cracking (FCC) oil slurry, the reaction activity between components with different chemical structures varies greatly, and excessive reactions are easily produced during heating treatment, resulting in a decrease in the secondary processing performance of the mesophase asphalt. Therefore, based on the properties of the catalytic cracking oil slurry, the field expects to develop a highly universal and flexibly controllable combined heat treatment process, which has important economic and social benefits.
[0004] For example, Chinese patent CN114940918A discloses a mesophase asphalt prepared from hydrocracking tail oil and a preparation method thereof, wherein the prepolymerized hydrocracking tail oil is mixed with asphalt in a certain proportion, and then the mesophase asphalt is obtained by co-carbonization treatment under high temperature and high pressure; however, due to the high reaction temperature, excessive carbonization reaction is easily generated during the treatment process, thereby affecting the spinnability of the mesophase asphalt. Another example is Chinese patent CN106147834A discloses a combined method for separating catalytic cracking oil slurry and preparing mesophase asphalt, wherein an extraction solvent is used to extract and separate the catalytic cracking oil slurry components under supercritical or subcritical conditions and perform hydrodesulfurization treatment, and then the components are mixed in different proportions to prepare the mesophase asphalt as a raw material, but there are defects such as complex process flow and low economic benefits, and it is difficult to achieve large-scale production. For example, Chinese patent CN113528178A discloses a method for preparing mesophase asphalt using catalytic cracking oil slurry, using catalytic cracking oil slurry as raw material, graphene as catalyst, and adopting a two-step high-temperature thermal polycondensation process to prepare mesophase asphalt; however, the mesophase content of the product prepared by this method is only 80%, and the softening point is relatively high, and the graphene particles added during the reaction cannot be removed, making secondary processing and utilization difficult.
[0005] Therefore, how to overcome the disadvantage of high ash content in catalytic cracking oil slurry and then develop a high-quality mesophase asphalt product is beneficial to the development of petroleum resources and has positive significance. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to provide a high-quality mesophase asphalt product to achieve the deep development of petroleum resources;
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned mesophase asphalt to overcome the disadvantage of high ash content in catalytic cracking oil slurry.
[0008] In order to solve the above technical problems, the present invention discloses a method for preparing an intermediate phase asphalt, comprising the steps of using catalytic cracking oil slurry as raw material, adding a magnetic organic iron macromolecular complex, and carrying out a catalytic polycondensation reaction in the presence of a heteropolyacid iron salt catalyst.
[0009] Specifically, in the preparation method of the mesophase asphalt, the magnetic organic iron macromolecular complex includes one or a mixture of sodium ferric gluconate complex, ferric hydroxide-sucrose complex or cyclodextrin macromolecular iron complex;
[0010] Preferably, the amount of the magnetic organic iron macromolecular complex added is 0.5-5wt% of the amount of the catalytic cracking oil slurry.
[0011] Specifically, in the preparation method of the mesophase asphalt, the heteropolyacid iron salt catalyst includes one or a mixture of ferrophosphite, ferrosiliconic acid or sodium ferrite;
[0012] Preferably, the amount of the heteropolyacid iron salt catalyst added is 1-10 wt % of the amount of the catalytic cracking oil slurry.
[0013] Specifically, in the preparation method of the mesophase asphalt, the temperature of the catalytic polycondensation reaction is 280-400° C., the reaction pressure is 2-4 MPa, and the reaction time is 100-180 min.
[0014] Specifically, the method for preparing the mesophase asphalt further comprises the step of separating the catalytic polycondensation reaction product to obtain the desired intermediate asphalt;
[0015] The separation step includes the step of using a thermal sedimentation process to separate the catalytic polycondensation reaction product by sedimentation under the assistance of a weak magnetic field.
[0016] Specifically, the preparation method of the mesophase asphalt is:
[0017] The strength of the weak magnetic field ranges from 1000 to 1800 A / m; and / or,
[0018] The temperature of the heat deposition process is 150-200°C.
[0019] Specifically, the method for preparing the mesophase asphalt further comprises the step of purifying the separated intermediate asphalt;
[0020] The purification step includes the step of extracting quinoline from the mesophase asphalt after sedimentation separation, and the step of removing quinoline by reduced pressure distillation.
[0021] Specifically, the preparation method of the mesophase asphalt is:
[0022] The temperature of the extraction step is 180-240°C; and / or,
[0023] The temperature of the reduced pressure distillation step is 120-160°C.
[0024] The invention also discloses high-quality intermediate asphalt prepared by the method.
[0025] The invention also discloses the use of the high-quality intermediate asphalt in preparing carbon materials.
[0026] The preparation method of the mesophase asphalt described in the present invention is based on the traditional catalytic cracking FCC oil slurry synthesis process, takes catalytic cracking (FCC) oil slurry as raw material, adds a small amount of magnetic organic iron macromolecular complex in the presence of heteropolyacid iron salt as catalyst, and adopts catalytic polycondensation to prepare the mesophase asphalt; and uses a weak magnetic field assisted thermal sedimentation process to sediment and separate the catalytic polycondensation product, and then extracts quinoline from the lower layer of anisotropic asphalt to remove impurities such as ash and iron catalyst in the asphalt, so as to obtain quinoline soluble mesophase asphalt with a softening point of 220-300°C, low impurity content and wide-area streamlined optical texture.
[0027] The preparation method of mesophase asphalt described in the present invention is aimed at the high ash content of catalytic cracking oil slurry, and a method of preparing mesophase asphalt by catalytic polycondensation of heteropolyacid iron salt is developed, and solid impurities are separated by thermal precipitation coupled with weak magnetic field, and high-quality quinoline-soluble mesophase asphalt is obtained by solvent extraction. The present invention integrates the preparation, purification and separation treatment of catalytic polycondensation reaction-mesophase components, and realizes the simultaneous removal of ash impurities and the regulation of mesophase components. It is a new and efficient integrated process for the preparation and purification of mesophase asphalt, which can meet the needs of preparing mesophase asphalt using aromatic-rich feedstock oils of different properties, especially suitable for feedstock oils with high ash content, and has the advantages of large operating space and high universality, laying a solid foundation for the preparation of high-quality mesophase asphalt and corresponding carbon materials.
[0028] The preparation method of mesophase asphalt of the present invention, in the reaction system, adds heteropolyacid iron salt as a catalyst to stimulate the activation of raw oil molecules, reduce the reaction temperature, avoid excessive condensation of mesophase asphalt molecules, and avoid the use of AlCl3 or BF3, which are highly corrosive and toxic and have high requirements on reaction equipment. At the same time, the iron salt can be used as a nucleating agent to induce the generation of mesophase asphalt components and improve the conversion rate.
[0029] In the preparation method of the mesophase asphalt described in the present invention, the addition of a small amount of magnetic organic iron macromolecular complex helps to improve the catalytic efficiency of the iron salt, and also helps to adsorb the mesophase components with higher molecular weight to improve the sedimentation efficiency; at a certain temperature, with the help of a weak magnetic field effect, the sedimentation rate of the magnetic organic iron molecular complex is accelerated, and the stratification of the isotropic phase and the anisotropic phase is promoted.
[0030] The preparation method of the mesophase asphalt of the present invention utilizes quinoline to extract the lower layer anisotropic product asphalt, completely removes the ash such as solid particles in the mesophase asphalt, and simultaneously utilizes vacuum distillation to recover quinoline to obtain high-quality mesophase asphalt with high mesophase content, low softening point and uniform molecular weight distribution. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.
[0032] Example 1
[0033] In a high-pressure reactor, 280 g of catalytic cracking oil slurry, 2.8 g of ferric phosphate and 1.4 g of sodium ferric gluconate complex were added and mixed, and the catalytic polycondensation reaction was carried out at a reaction temperature of 280° C. and a reaction pressure of 2 MPa for 120 min to obtain a catalytic polycondensation reaction product.
[0034] After the reaction is completed, the magnetic field generator is adjusted to make the magnetic field strength reach 1000 m / A, the temperature is adjusted to 150° C. for sedimentation treatment for 100 min, and then the reactor is placed in cold water for rapid cooling.
[0035] The anisotropic asphalt at the bottom of the reactor was taken for quinoline extraction at 180°C, and then the quinoline soluble component was subjected to reduced pressure distillation at 120°C to recover the quinoline solvent. The quinoline soluble asphalt was placed in a vacuum oven at 100°C for 2 hours to further remove the residual quinoline solvent.
[0036] It was determined that the softening point of the quinoline soluble mesophase asphalt obtained through the above treatment process was 270°C and the mesophase asphalt content was 89%.
[0037] Example 2
[0038] In a high-pressure reactor, 280 g of catalytic cracking oil slurry, 5.6 g of ferric phosphate and 2 g of sodium ferric gluconate complex were added and mixed, and the catalytic polycondensation reaction was carried out at a reaction temperature of 350° C. and a reaction pressure of 2 MPa for 180 min to obtain a catalytic polycondensation reaction product.
[0039] After the reaction is completed, the magnetic field generator is adjusted to make the magnetic field strength reach 1300 m / A, the temperature is adjusted to 150° C. for sedimentation treatment for 120 min, and then the reactor is placed in cold water for rapid cooling.
[0040] The anisotropic asphalt at the bottom of the reactor was taken for quinoline extraction at 190°C, and then the quinoline soluble component was subjected to reduced pressure distillation at 120°C to recover the quinoline solvent. The quinoline soluble asphalt was placed in a vacuum oven at 100°C for 2 hours to further remove the residual quinoline solvent.
[0041] It was determined that the softening point of the quinoline soluble mesophase asphalt obtained through the above treatment process was 283°C and the mesophase content was 93%.
[0042] Example 3
[0043] In a high-pressure reactor, 280 g of catalytic cracking oil slurry, 8.4 g of ferric phosphate and 4 g of sodium ferric gluconate complex were added and mixed, and the catalytic polycondensation reaction was carried out at a reaction temperature of 400° C. and a reaction pressure of 4 MPa for 180 min to obtain a catalytic polycondensation reaction product.
[0044] After the reaction was completed, the magnetic field generator was adjusted to make the magnetic field strength reach 1800 m / A, and the reactor was subjected to sedimentation treatment at 160° C. for 180 min, and then the reactor was placed in cold water for rapid cooling.
[0045] The anisotropic asphalt at the bottom of the reactor was taken for quinoline extraction at 180°C, and then the quinoline soluble component was subjected to reduced pressure distillation at 120°C to recover the quinoline solvent. The quinoline soluble asphalt was placed in a vacuum oven at 100°C for 2 hours to further remove the residual quinoline solvent.
[0046] It was determined that the softening point of the quinoline soluble mesophase asphalt obtained through the above treatment process was 292°C and the mesophase content was 95%.
[0047] Example 4
[0048] In a high-pressure reactor, 280 g of catalytic cracking oil slurry, 2.8 g of ferric phosphate and 6 g of ferric hydroxide-sucrose complex were added and mixed, and the catalytic polycondensation reaction was carried out at a reaction temperature of 350° C. and a reaction pressure of 3 MPa for 150 min to obtain a catalytic polycondensation reaction product.
[0049] After the reaction is completed, the magnetic field generator is adjusted to make the magnetic field strength reach 1500 m / A, the temperature is adjusted to 200° C. for sedimentation treatment for 100 min, and then the reactor is placed in cold water for rapid cooling.
[0050] The anisotropic asphalt at the bottom of the reactor was taken for quinoline extraction at 240°C, and then the quinoline soluble component was subjected to reduced pressure distillation at 160°C to recover the quinoline solvent. The quinoline soluble asphalt was placed in a vacuum oven at 100°C for 2 hours to further remove the residual quinoline solvent.
[0051] It was determined that the softening point of the quinoline soluble mesophase asphalt obtained through the above treatment process was 285°C and the mesophase content was 94%.
[0052] Example 5
[0053] In a high-pressure reactor, 280 g of catalytic cracking oil slurry, 2.8 g of iron phosphate and 8 g of cyclodextrin macromolecular iron complex were added and mixed, and the catalytic polycondensation reaction was carried out at a reaction temperature of 350° C. and a reaction pressure of 3 MPa for 150 min to obtain a catalytic polycondensation reaction product.
[0054] After the reaction is completed, the magnetic field generator is adjusted to make the magnetic field strength reach 1500 m / A, the temperature is adjusted to 200° C. for sedimentation treatment for 100 min, and then the reactor is placed in cold water for rapid cooling.
[0055] The anisotropic asphalt at the bottom of the reactor was taken for quinoline extraction at 240°C, and then the quinoline soluble component was subjected to reduced pressure distillation at 160°C to recover the quinoline solvent. The quinoline soluble asphalt was placed in a vacuum oven at 100°C for 2 hours to further remove the residual quinoline solvent.
[0056] It was determined that the softening point of the quinoline soluble mesophase asphalt obtained through the above treatment process was 293°C and the mesophase content was 96%.
[0057] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing mesophase asphalt, characterized in that: The method comprises the steps of using catalytic cracking oil slurry as raw material, adding magnetic organic iron macromolecular complex, and carrying out catalytic polycondensation reaction in the presence of heteropolyacid iron salt catalyst.
2. The method for preparing mesophase pitch according to claim 1, characterized in that: The magnetic organic iron macromolecular complex comprises one or a mixture of sodium ferric gluconate complex, ferric hydroxide-sucrose complex or cyclodextrin macromolecular iron complex; Preferably, the amount of the magnetic organic iron macromolecular complex added is 0.5-5wt% of the amount of the catalytic cracking oil slurry.
3. The method for preparing mesophase pitch according to claim 1 or 2, characterized in that: The heteropolyacid iron salt catalyst includes one or a mixture of ferrophosphite, ferrosiliconic acid or sodium ferrite; Preferably, the amount of the heteropolyacid iron salt catalyst added is 1-10 wt % of the amount of the catalytic cracking oil slurry.
4. The method for preparing mesophase asphalt according to any one of claims 1 to 3, characterized in that: The temperature of the catalytic polycondensation reaction is 280-400° C., the reaction pressure is 2-4 MPa, and the reaction time is 100-180 min.
5. The method for preparing mesophase asphalt according to any one of claims 1 to 4, characterized in that: The method further comprises the step of separating the catalytic polycondensation reaction product to obtain the desired intermediate asphalt; The separation step includes the step of using a thermal sedimentation process to separate the catalytic polycondensation reaction product by sedimentation under the assistance of a weak magnetic field.
6. The method for preparing mesophase pitch according to claim 5, characterized in that: The strength of the weak magnetic field ranges from 1000 to 1800 A / m; and / or, The temperature of the heat deposition process is 150-200°C.
7. The method for preparing mesophase pitch according to claim 5 or 6, characterized in that: The method further comprises the step of purifying the separated intermediate asphalt; The purification step includes the step of extracting quinoline from the mesophase asphalt after sedimentation separation, and the step of removing quinoline by reduced pressure distillation.
8. The method for preparing mesophase pitch according to claim 7, characterized in that: The temperature of the extraction step is 180-240°C; and / or, The temperature of the reduced pressure distillation step is 120-160°C.
9. High-quality intermediate asphalt prepared by the method according to any one of claims 1 to 8.
10. Use of the high-quality intermediate pitch according to claim 9 for preparing carbon materials.
Citation Information
Patent Citations
Combination method for separating catalytic cracking oil slurry and preparing mesophase pitch
CN106147834A
Method for preparing mesophase asphalt by using catalytic cracking slurry oil
CN113528178A
Mesophase pitch prepared from hydrogenation tail oil and method thereof
CN114940918A